Neuroprotection by alpha-lipoic acid in streptozotocin-induced diabetes - Baydas, G.; Donder, E.; Kiliboz, M.; Sonkaya, E.; Tuzcu, M.; Yasar, A.; Nedzvetskij, V.S. (My University, 2004)
Glial cells provide structural and metabolic support for neurons, and these cells become reactive to any insult to the central nervous system. The streptozotocin (STZ) rat model was used to study glial reactivity and the prevention of gliosis by alpha-lipoic acid (alpha-LA) administration. The expression of glial fibrillary acidic protein (GFAP), S100B protein, and neuron specific enolase (NSE) was determined as well as lipid peroxidation (LPO) and glutathione (GSH) levels in some brain tissues. Western blot analyses showed GFAP, S100B, and NSE levels significantly increased under STZ-induced diabetes in brain, and LPO level increased as well. Administration of alpha-LA reduced the expression both of glial and neuronal markers. In addition, alpha-LA significantly prevented the increase in LPO levels found in diabetic rats. GSH levels were increased by the administration of alpha-LA. This study suggests that alpha-LA prevents neural injury by inhibiting oxidative stress and suppressing reactive gliosis.
Keywords: Alpha-lipoic acid; Diabetes; Glial fibrillary acidic protein; Neuron specific enolase; S100B protein